Efektivitas Eksekusi Putusan PTUN dalam Sengketa Administratif Partai Politik: Analisis Putusan PTUN Jakarta No: 455/G/SPPU/2022/PTUN.JKT - Muhammad Dafa Fauzan (Uniku Law Review, 2025)
This article was written to fulfill the requirements of the State Administrative Court Procedural Law course taught by Prof. Dr. Suwari Akhmadian, S.H., M.H., with the aim of analyzing the effectiveness of the execution of PTUN decisions in political party administrative disputes based on the Jakarta PTUN Decision Number 455/G/SPPU/2022/PTUN.JKT. This research uses normative legal methods with a statutory approach and case studies to examine the provisions of Article 116 of Law No. 5 of 1986 in conjunction with Law No. 9 of 2004 in conjunction with Law No. 51 of 2009 and their application in practice. The results of the study indicate that although the normative framework for decision execution is clear, its implementation still faces serious obstacles in the form of a lack of technical regulations, weak inter-agency coordination, and political resistance in political party management disputes. The study's conclusion emphasizes the need to strengthen executorial regulations and the legal culture of state administrative officials so that the execution of PTUN decisions can be effective, provide legal certainty, and realize optimal legal protection.